A new species of the genus Leptolalax (Anura: Megophryidae) from Guangxi, China - Yuan, Zhiyong; Sun, Ruida; Chen, Jinmin; Rowley, Jodi J. L.; Wu, Zhengjun; Hou, Shaobing; Che, Jing (Zootaxa, 2017)
We describe a new species of megophryid frog from Maoershan Nature Reserve in southern China. Leptolalax maoershanensis sp. nov. is distinguished from its congeners by a combination of the following morphological characters: medium size (SVL 25.2–30.4 mm in eight adult males and 29.1 mm in one adult female); head longer than wide; externally distinct tympanum; distinct black supratympanic line present; dorsal skin shagreened with small tubercles and longitudinal folds; distinct dark spots on the flank; creamy-white chest and belly with irregular black spots; grey-pinkish to dark brownish-violet ventral skin of limbs with numerous whitish speckles; distinct ventrolateral glands forming a white line; finger webbing and fringes absent; toe webbing rudimentary and lateral fringes narrow; longitudinal ridges indistinct under toes and not interrupted at the articulations; and a bicolored iris. The new species differs from all known congeners by an uncorrected p-distance of >6.6% at the 16S rRNA gene fragment examined, and phylogenetic analysis clusters the new species with L. laui and L. liui. At present, the new species is known from montane small bamboo forest in Maoershan Nature Reserve at about 1550 m elevation.